1980
DOI: 10.3133/pp1090
|View full text |Cite
|
Sign up to set email alerts
|

Ordovician and Silurian Phi Kappa and Trail Creek formations, Pioneer Mountains, central Idaho: Stratigraphic and structural revisions, and new data on graptolite faunas

Abstract: Recent geologic mapping in the northern Pioneer Mountains combined with the identification of graptolites from 116 new collections indicate that the Ordovician and Silurian Phi Kappa and Trail Creek Formations occur in a series of thrust-bounded slices within a broad zone of imbricate thrust faulting. Though confirming a deformational style first reported in a 1963 study by Michael Churkin, our data suggest that the complexity and regional extent of the thrust zone were not previously recognized. Most previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Our observation is that an Antler fabric is present in many, but not all, outcrops of Devonian and older strata west of the Trail Creek fault but is not present east of the fault. The presence of an Antler fabric in central Idaho has been long debated (Dover, 1980), and the nature of such a fabric requires further study.…”
Section: Paleozoic Syngenetic Stratiform Mineralization and The Antler Orogenymentioning
confidence: 99%
See 4 more Smart Citations
“…Our observation is that an Antler fabric is present in many, but not all, outcrops of Devonian and older strata west of the Trail Creek fault but is not present east of the fault. The presence of an Antler fabric in central Idaho has been long debated (Dover, 1980), and the nature of such a fabric requires further study.…”
Section: Paleozoic Syngenetic Stratiform Mineralization and The Antler Orogenymentioning
confidence: 99%
“…Based on the presence of a Mississippian-age flysch trough (Copper Basin Formation) containing clasts derived from the Milligen Formation, and Nilsen (1977) suggested that the Milligen Formation was thrust eastward to form a highland during the Late Devonian to Early Mississippian Antler orogeny. The thrust fault that accommodated this shortening cannot, however, be conclusively located in south-central Idaho (Dover, 1980). If it is present in the Hailey 1 x2 quadrangle, it may be concealed beneath the outcrop belt of upper Paleozoic Wood River Formation in the Boulder Mountains (Roberts and Thomasson, 1964), or it may have been reactivated to become the Cretaceous Pioneer thrust fault (Wust, 1986) or the early Eocene(?)…”
Section: Paleozoic Syngenetic Stratiform Mineralization and The Antler Orogenymentioning
confidence: 99%
See 3 more Smart Citations